Flexible hard Al-Si-N films for high temperature operation; Surface and Coatings Technology; Vol. 307, pt. B: Electrochemical and Plasma Electrolytic Modification of Metal Surfaces - Musil Y. Yindrikh; Remnev (Remnyov) G. E. Gennady Efimovich; Legostaev V. N. Viktor Nikiforovich; Uglov V. V. Vladimir Vasilievich; Lebedinsky A. M. Aleksey Mikhaylovich; Lauk A. L. Aleksandr Lukyanovich; Prochazka J .; Haviar S.; Smolyanskiy (Smolyansky, Smolyanskii) E. A. Egor Aleksandrovich (2016, 2016)
Title screen